CORROSION BEHAVIOUR OR TIN IN CARBOXYLIC ACID SOLUTIONS CONTAINING NO;, NO; AND CI-ANIONS AT DIFFERENT pH VALUES (Biological Sciences - PJSIR, 2022)
The corrosion behaviour of pure tin in deaerated solutions of oxalic, tartaric and citric acids in the presence andabsence of NO;, NO~ and cr anions were studied by means of potential-time measurements, corrosion rate andgalvanostatic technique at thepHrange 2.5 - 6.5 forO.1Mof the three tested acids. AtpH4.5 there is amaximum negativepotential for oxalic acid and at pH 5.5 for tartaric and citric acids. From pH 2.5 to 4.5, the corrosion mechanism isanodically controlled by the reaction of Sn+2ion with the anion ofthe tested acids. AtpH 5.5 the corrosion of tin is reducedwhich may be due to the formation of a film on the tin electrode resulting from the hydrolysis of tin complex species.,The potential of the tin electrode in the three tested acid solutions tends to be shifted to the less negative values in thepresen~e ofaddirives NO;, N03 and CI anions at pH 4.5.